Business Process Management 13th International Conference, BPM 2015, Innsbruck, Austria, August 31 -- September 3, 2015, Proceedings - Motahari-Nezhad, Hamid Reza; Recker, Jan; Weidlich, Matthias (Information Systems and Applications, incl. Internet/Web, and HCI, 2015)
This book constitutes the proceedings of the 13th International Conference on Business Process Management, BPM 2015, held in Innsbruck, Austria, in August/September 2015. The 21 regular papers, 7 short papers and 2 inductrial papers included in this volume were carefully reviewed and selected from 125 submissions. The papers are organized in topical sections on runtime process management, process modeling, process modeling discovery, business process models and analytics, BPM in industry, process compliance and deviations, energing and practical areas of BPM, and process monitoring.